Public Expenditure Review of the Basic Education Sector in Botswana - World Bank; Government of Botswana; UNICEF (World Bank, Washington, DC, 2020)
This Basic Education Public Expenditure Review (PER) was performed at the request of the GoB to assess fiscal expenditure in education and provide recommendations that could improve the performance of the country’s school system. More specifically, the PER assessed the adequacyand sustainability of public education spending, the efficiency and effectiveness of resourcesused, the equity of education expenditures, and key management and governance issues in theeducation sector. The analysis focused on the efficiency of budget allocations across educationlevels and regions; educational outcomes, including student progression and dropout rates; cognitive outcomes, as measured by national examinations and assessments; equity of access; resources and outcomes across regions; gender and income groups; and the institutional context.